Legal Protection of Franchisee in Franchise Contract Which Franchisor Unilaterally Terminates - Wulandari, Retno (Universitas Wijaya Kusuma Surabaya, 2021)
The Franchisor and the Franchisee's engagement tends to be based on the value of business profits alone. The document that becomes evidence (franchise agreement) tends to be poorly understood by the Franchisee, which can cause legal problems for him. One of the legal issues that can occur is the unilateral termination of the Franchisor to the Franchisee. Franchise agreements tend to be standardized, which comes from the Franchisor. These conditions make the Franchisee obliged to understand the agreement's contents well so that the franchise agreement is not terminated unilaterally by the Franchisor. This study aims to find out and analyze how legal protection for franchisee is based on franchise agreement. This research method is a normative legal research approach. The result of this study is unilateral termination of the franchise agreement will undoubtedly cause various legal problems for the parties bound in the franchise agreement.Keywords: Termination, Agreement, Franchise.